Conophylline Promotes the Proliferation of Immortalized Mesenchymal Stem Cells Derived from Fetal Porcine Pancreas (iPMSCs) - Hui-ru ZHANG; Dan LI; Hui CAO; Xiao LÜ; Yuan-kui CHU; Yao-fu BAI; Ya-ping JIN; Sha PENG; Zhong-ying DOU; Jin-lian HUA (Journal of Integrative Agriculture, 2013)
Conophylline, is a bis (indole) alkaloid consisting of two pentacyclic aspidosperma skeletons, isolated from Tabernaemontana divaricata, which has been found to induce b-cell differentiation in rat pancreatic acinar carcinoma cells and in cultured rat pancreatic tissue. However, the precise role of conophylline in the growth and survival of immortalized pancreatic mesenchymal stem cells (iPMSCs) derived from fetal porcine pancreas were not understood at present. To determine whether this molecule is involved in controlling the proliferation of iPMSCs, we examined the effects of conophylline on iPMSCs. We found that conophylline can robustly stimulate iPMSCs proliferation, even promote their potential differentiation into islet-like clusters analyzed by cell counting, morphology, RT-PCR and real-time PCR, Western blotting, glucose-stimulated insulin release and insulin content analysis. The effects of conophylline were inhibited by LY294002, which is the inhibitor of the PI3K pathway. These results suggest that conophylline plays a key role in the regulation of cell mass proliferation, maintenance of the undifferentiated state of iPMSCs and also promotes iPMSCs differentiated into insulin-producing cells.